2017
DOI: 10.3390/md15100314
|View full text |Cite
|
Sign up to set email alerts
|

Identification of (Z)-2,3-Diphenylacrylonitrile as Anti-Cancer Molecule in Persian Gulf Sea Cucumber Holothuria parva

Abstract: Hepatocellular carcinoma (HCC), also named cancerous hepatoma, is the most common type of malignant neoplasia of the liver. In this research, we screened the Persian Gulf sea cucumber Holothuria parva (H. parva) methanolic sub-fractions for the possible existence of selective toxicity on liver mitochondria isolated from an animal model of HCC. Next, we purified the most active fraction. Thus the structure of the active molecule was identified. HCC was induced by diethylnitrosamine (DEN) and 2-acetylaminofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Many studies have reported that sea cucumber extract contains several compounds, including mono sulfated tritepenoid glycoside Frondoside A, disulfated glycoside Frondoside B, trisulfated glycoside Frondoside C, eicosapentaenoic acid, fucosylated chondroitin sulfate, nobiliside D, 12-methyltetradecanoic acid, sphingoid and canthaxanthin/astaxanthin, that have induced apoptosis in solid cancers, including breast, liver, renal, cervical, lung, and colorectal cancer cells [15,24,25,26]. Amidi et al reported that (Z)-2,3-diphenylacrylonitrile molecules isolated from Persian Gulf SC were identified as potential anti-cancer agents [27]. In our study, the crude and fractionated sulfated fucan from the sea cucumber, Stichopus japonicas , was used to investigate its anti-tumor activity [17].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that sea cucumber extract contains several compounds, including mono sulfated tritepenoid glycoside Frondoside A, disulfated glycoside Frondoside B, trisulfated glycoside Frondoside C, eicosapentaenoic acid, fucosylated chondroitin sulfate, nobiliside D, 12-methyltetradecanoic acid, sphingoid and canthaxanthin/astaxanthin, that have induced apoptosis in solid cancers, including breast, liver, renal, cervical, lung, and colorectal cancer cells [15,24,25,26]. Amidi et al reported that (Z)-2,3-diphenylacrylonitrile molecules isolated from Persian Gulf SC were identified as potential anti-cancer agents [27]. In our study, the crude and fractionated sulfated fucan from the sea cucumber, Stichopus japonicas , was used to investigate its anti-tumor activity [17].…”
Section: Discussionmentioning
confidence: 99%
“…exhibited cytotoxicity and were strong kinase inhibitors, 710 and (Z)-2,3diphenylacrylonitrile (Holothuria parva) caused an increase in ROS generation and collapse of the mitochondrial membrane potential in hepatocellular carcinoma cells. 711 Puried spinochromes, naphthoquinones from urchins, exhibit wide ranging activities against bacteria, as antioxidants, as pro-inammatory agents and as cytotoxins. 712 Mature eggs of the sand dollar Scaphechinus mirabilis contain a jelly coat bearing pigment cells which contain spinochromes D and E, and to a lesser degree, spinochrome A and echinochrome A.…”
Section: Echinodermsmentioning
confidence: 99%
“…However, the apoptosis rate measured by flow cytometry was not statistically significant, which is similar to the results of a study using human umbilical vein endothelial cells, which found that AGF failed to induce cell apoptosis ( 26 ). Extensive studies have indicated that apoptosis and proliferation are mediated by increased levels of ROS ( 27 ). ROS plays a dual role in tissue injury, as moderate levels of ROS promote cell survival and proliferation, whereas excessive ROS production can directly induce necrocytosis ( 28 ).…”
Section: Discussionmentioning
confidence: 99%